2013
DOI: 10.1113/jphysiol.2013.263228
|View full text |Cite
|
Sign up to set email alerts
|

Optical determination of intracellular water in apoptotic cells

Abstract: Key points• Determination of intracellular water can be achieved by a combination of brightfield and transmission-through-dye imaging, all realized on a standard transmission microscope.• The method permits sensitive detection of water loss in cells exposed to apoptotic agents.• Cell water measurements are not affected by separation of apoptotic bodies and can be applied to samples where measurements of cell volume alone would be insufficient.Abstract Intracellular water plays a critical role in apoptotic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Refractility is known to increase with increased concentrations of proteins and other macromolecules but shows little or no change in response to changes in salt concentration, changes in pH, denaturation of proteins, or digestion of proteins to amino acids (34). The refractility of mammalian cells also increases during apoptosis, and it has been suggested that this increase reflects a decrease in intracellular water and a corresponding increase in the concentration of proteins and other macromolecules in the cell (35). The increased refractility of apoptotic cells observed in C. elegans could also result from an increase in the concentration of macromolecules.…”
Section: Significancementioning
confidence: 99%
“…Refractility is known to increase with increased concentrations of proteins and other macromolecules but shows little or no change in response to changes in salt concentration, changes in pH, denaturation of proteins, or digestion of proteins to amino acids (34). The refractility of mammalian cells also increases during apoptosis, and it has been suggested that this increase reflects a decrease in intracellular water and a corresponding increase in the concentration of proteins and other macromolecules in the cell (35). The increased refractility of apoptotic cells observed in C. elegans could also result from an increase in the concentration of macromolecules.…”
Section: Significancementioning
confidence: 99%
“…As mentioned above, apoptotic cells can reduce their volume by loss of water (which is the essence of AVD) or by separation of apoptotic bodies. It is frequently stated that formation of apoptotic bodies occurs only during the final stages of apoptosis, but this is not always the case; for example, the protein kinase inhibitor staurosporine, which is frequently used to study AVD, tends to cause rapid cell fragmentation in diverse cell types (86). However, reliable detection of dissociated apoptotic bodies is far from simple, and there have been few detailed investigations of the methodology of such an assay (133).…”
Section: Undetected Apoptotic Body Releasementioning
confidence: 99%
“…This is followed by formation of the blebs at the cell surface due to the separation of the plasma membrane from cytoskeleton. [34][35][36][37] The observational experiment displayed that the higher b-diiminato Mn III complex concentration exposed to the MCF-7 and MDA-MB-231 cells, the more the destructive changes in the cell morphology compared to untreated cells. 3.5.2.…”
Section: The Cytotoxic Effects Of B-diiminato Mn III Complex Using Ldmentioning
confidence: 99%